Forces acting on the clavicle during shoulder abduction, forward humeral flexion and activities of daily living. (October 2019) - Hoogervorst, P.; Bolsterlee, B.; Pijper, M.; Aalsma, A.; Verdonschot, N.
Abstract: Background: The forces acting on the human clavicle in vivo are difficult if not impossible to measure. The goal of this study is to quantify the forces acting on the human clavicle during shoulder abduction, forward humeral elevation and three activities of daily living using the Delft Shoulder and Elbow Model. Methods: The Delft Shoulder and Elbow Model and a computed tomography scan of a clavicle were used to calculate the forces and moments acting on the entire clavicle and on three planes within the middle third of the clavicle during the simulated movements. Findings: The largest resultant force simulated across the clavicle was 126 N during abduction. Maximum resultant moments of 2.4 Nm were identified during both abduction and forward humeral elevation. The highest forces in the middle third of the clavicle were of a compressive nature along the longitudinal axis of the clavicle, increasing to 97 N during forward humeral elevation and 91 N during abduction. Forces in opposite direction along the y-axis were identified on either side of the conoid ligament. The three simulated activities of daily living had similar ranges of forces and moments irrespective of the sagittal plane in which these activities were performed. Interpretation: Peak forces occurred at different locations on the middle third of the clavicle during different movements. The results create an understanding of the forces and their distribution across the clavicle during activities of daily living. These data may be helpful in the development of clavicular fixation devices. Level of evidence: Biomechanical study. Highlights: The highest forces were simulated along the x-axis, increasing to 118 N during abduction. The largest resultant moment simulated across the clavicle was 2.4 Nm during abduction and forward elevation. Forces in opposite direction along the y-axis were identified on either side of the conoid ligament. Similar forces and moments during activities of daily living were identified irrespective its sagittal plane. The forces and moments during activities of daily living activities occur at different locations on the clavicle.